P61 Factors influencing improved lung cancer resection rates 2006 2012; A single centre case cohort study. (14th November 2013) - Selvaraj, S; Rajesh, P; Naidu, B; Kalkat, M; Woolhouse, IS
Abstract : Background: Surgical resection rates for lung cancer have increased steadily over the last decade. There are a number of possible explanations for this increase which include: earlier presentation, earlier detection and an increase capacity and/or willingness for thoracic surgeons to operate. The aim of this study is to identify which of these factors are associated with the increase in surgical resection seen at our institution, in particular, whether the increased use of CT scanning across all areas of medicine, e.g. cardiac CT, has impacted on the rate of incidentally detected operable lung cancers. Methods: We used data submitted to the national lung cancer audit (excluding Mesothelioma) to identify changes in performance status (PS), lung function and stage at presentation from 2006 to 2012. We then performed a retrospective case note analysis of patients who received surgery to identify the proportion of surgical cases in whom the lung cancer had been detected incidentally i.e. on imaging not performed to investigate suspected lung cancer. Statistical comparisons were performed using chi-squared and ANOVA tests. Results: Mean age was 71 years and did not change across the study period. The remaining results are summarised in the table. Surgical resection rates increased significantly during the study period but there was no change in performance status or lung function at presentation. There was a significant increase in the proportion of patients presenting with early stage disease however the proportion of operable lung cancers detected incidentally did not change during the study period. Conclusion: The increase in surgical resection rates seen at our institution appears to relate to a stage shift at presentation. Although incidentally detected lung cancers make up a significant proportion of operable lung cancers, this does not account for the stage shift. An alternative explanation is the impact of the national awareness and early diagnosis campaign (formally launched in 2008) prompting patients to present earlier and GPs to refer sooner.